ANALYSIS OF THE INFLUENCE OF INTEGRATED MARKETING COMMUNICATION TEIN THE DECISION OF TOURISTS TO VISIT IN KCENTRAL ACEH REGENCY - Mamfalutin; Sugih Arto Pujangkoro; Beby Karina Fawzeea Sembiring (RADJA PUBLIKA, 2025)
This research aims to analyze the influence of Integrated Marketing Communication on tourists' decision to visit Central Aceh, with a focus on three tourist attractions: Arung Jeram Lukup Badak, Pantan Teron, and Pante Manye. The independent variables in this study are advertising, personal selling, sales promotion, public relations, and events and experience, while the dependent variable is the decision to visit. The research type employed is causal associative research with a quantitative approach. Primary data was collected through questionnaires distributed to tourists visiting the mentioned attractions. The sample was drawn from the population of respondents visiting these tourist attractions using accidental sampling. Data analysis was conducted using multiple linear regression to test the partial influence of each independent variable on the decision to visit and the simultaneous influence of all independent variables. The results show that, individually, the independent variables advertising, sales promotion, and public relations do not have a significant effect on tourists' decision to visit attractions in Central Aceh. Personal selling and events and experience, on the other hand, significantly influence tourists' decision to visit attractions in Central Aceh. Simultaneously, all these independent variables also significantly influence the decision to visit. From these findings, it can be concluded that the effective implementation of IMC strategies plays a crucial role in increasing tourists' decisions to visit Central Aceh, especially at the specified tourist locations. The implications of these findings can serve as a foundation for tourism managers and stakeholders to enhance the application of IMC to increase the attractiveness and visits of tourists to the region.